1993
DOI: 10.1073/pnas.90.12.5672
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in prokaryotes: luciferase as a reporter of circadian gene expression in cyanobacteria.

Abstract: We have used a luciferase reporter gene and continuous automated monitoring of bioluminescence to demonstrate unequivocally that cyanobacteria exhibit circadian behaviors that are fundamentally the same as circadian rhythms of eukaryotes. We also show that these rhythms can be studied by molecular methods in Synechococcus sp. PCC7942, a strain for which genetic transformation is well established. A promoterless segment of the Vibrio harveyi luciferase structural genes (luxAB) was introduced downstream of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
349
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(363 citation statements)
references
References 20 publications
8
349
0
Order By: Relevance
“…By fusing the psbA1 promoter, which drives expression of a component of photosystem II, to a promoterless luxAB gene cassette, transcription from this promoter was shown to be under circadian control in S. elongatus PCC 7942 (Kondo et al, 1993). A similar approach was used to show that expression from the dnaK promoter was rhythmic in Synechocystis sp.…”
Section: Rhythmic Clock Outputs In Cyanobacteriamentioning
confidence: 99%
“…By fusing the psbA1 promoter, which drives expression of a component of photosystem II, to a promoterless luxAB gene cassette, transcription from this promoter was shown to be under circadian control in S. elongatus PCC 7942 (Kondo et al, 1993). A similar approach was used to show that expression from the dnaK promoter was rhythmic in Synechocystis sp.…”
Section: Rhythmic Clock Outputs In Cyanobacteriamentioning
confidence: 99%
“…After the colonies on plates had been exposed to n-decyl aldehyde vapour for 3 min, the luminescence was determined as described by Kondo et al (1993;.…”
Section: Measurement Of Luminescence From Luciferasementioning
confidence: 99%
“…Cyanobacteria are the simplest organisms known to exhibit circadian rhythms. Thus, the cyanobacterium Synechococcus elongatus PCC 7942 (hereafter, Synechococcus) is an experimental model for the study of molecular mechanisms underlying these types of clocks (Kondo et al 1993). Saturation mutagenesis revealed that three adjacent genes (kaiA, kaiB, and kaiC) and their protein products are essential for circadian rhythm generation.…”
Section: Introductionmentioning
confidence: 99%